An Empirical Investigation of Elementary Art Teachers’ Satisfaction and Continuance Intention to Use E-Learning Systems in Chongqing, China - Li, Beizhen (Scholar: Human Sciences, 2024)
Purpose: This essay aims to assess critical factors that significantly impact the satisfaction and continuance intention of art teachers from primary schools in Chongqing Province of China for online education. In the research framework, it presents the causal relationship between engagement, course structure, system quality, information quality, service quality, perceived usefulness, satisfaction, and continuance intention. Research design, data, and methodology: The researcher applied a quantitative method to distribute the quantitative questionnaire to 500 elementary art teachers at 20 schools. The sampling strategies are used to collect the data, including judgmental, quota and convenience sampling. Before the data collection, the expert rating of the item's index–objective congruence (IOC) and pilot test for 50 respondents have been tested. This study employed a structural equation model (SEM) and confirmatory factor analysis (CFA). Result: Six out of eight hypotheses were supported. Perceived usefulness and satisfaction significantly impact continuance intention. There are non-supported relationships between course structure, sytem quality and satisfaction. Conclusions: Administrators need to pay close attention to the elements that greatly influence satisfaction in order for primary school art teachers to acknowledge and recognize the effectiveness of online education. They should also consider the research's findings when adjusting or reforming correlated instruction.